Research and innovation policies and productivity growth - Reinhilde Veugelers (Bruegel, 2021)
We review the evidence on the impact of public intervention on private research and innovation, and how research and innovation and R&I policies affect growth in the applied macro models most commonly used in European Union policy analysis. The evidence suggests that R&I grants and R&I tax credits can have positive effects in terms of stimulating investment in innovation. In terms of the impact of public R&I interventions on economy-wide GDP growth and jobs, the available applied macro models predict positive effects over the long term. It therefore takes time before short-term negative effects associated with reallocations of high-skilled labour from other productive activities to generate the extra innovations, and the negative effects from displacing older, more labour-intensive production processes, are compensated for. To the question of whether R&I policies can serve to power growth, the answer can only be a timid yes at this stage. R&I policies certainly have the potential, but still too little is known of what drives their actual effects. More micro and macro evaluations are still needed.
Keywords: 330